A reciprocal binary mixture of protic/aprotic ionic liquids as a deep eutectic solvent: physicochemical behaviour and application towards agarose processing. Issue 120 (18th November 2015) - Bharmoria, Pankaj; Damarla, Krishnaiah; Trivedi, Tushar J.; Malek, Naved I.; Kumar, Arvind
Abstract : Apart from structural tuning, the desired properties of ionic liquids (IL) can be achieved through judicious mixing of two or more ionic liquids. Abstract : Apart from structural tuning, the desired properties of ionic liquids (IL) can be achieved through judicious mixing of two or more ionic liquids. Herein we have investigated the alterations in the physicochemical properties of protic/aprotic ILs, (2-hydroxyethylammonium formate/1-butyl-3-methylimidazolium chloride) upon reciprocal binary mixing. Melting point analysis of the mixtures at various mole fractions showed their deep eutectic solvent nature. The variation in physical properties like density, speed of sound, and viscosity have been measured and utilized to derive the volume of mixing, isentropic compressibility, and activation energy of the viscous flow. Unlike the binary mixtures of ILs having common cations or anions, the investigated reciprocal binary mixture showed significant non-ideality, normally desired to take advantage of improved solvent properties. The polarity and ion–ion interactions have been studied through solvatochromic parameters (normalized Reichardt's parameter, dipolarity/polarizability, and hydrogen bond donor and acceptor coefficients) derived using solvatochromic probes. The prepared binary mixtures have been utilized for the dissolution of a gelling biopolymer agarose and formation of ionogels. Dissolution of agarose has been correlated with the solvatochromic parameters and the viscoelastic behaviour of ionogels is discussed in light of rheological measurements. The work gives fundamentally useful insights into tuning the properties of ILs for a specific application purpose.